2010
DOI: 10.1016/j.solmat.2010.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic evaluation of the nanostructuring approach to chalcopyrite-based intermediate band materials

Abstract: ARTICLE INFO ABSTRACT Keywords:Chalcopyrite Nanostructures Solar cells Nanostructured chalcopyrite compounds have recently been proposed as absorber materials for advanced photovoltaic devices. We have used photoreñectance (PR) to evalúate the impact of interdiffusion phenomena and the presence of native defects on the optoelectronic properties of such materials. Two model material systems have been analyzed: (i) thin layers of CuGaSe 2 (£ g =1.7 eV) and CuInSe 2 (1.0 eV) in a wide/low/wide bandgap stack that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In this approach, a QD superlattice is embedded in a semiconductor matrix with a larger band gap. In this direction, Marrón et al studied the potential formation of an intermediate band, by the insertion of CIS, CISe, CuGaS 2 , or CuGaSe 2 NCs in a host material, and concluded that defects may impose limits to the practical realization of QD-based intermediate band devices with these materials. ,, Ojajärvi et al studied the formation of an intermediate band structure by inserting CISe QDs within a CuGaS 2 matrix and calculated that this structure could provide a maximum PCE of 61% . The experimental feasibility of the growth of this nanocomposite was further demonstrated by molecular beam epitaxy and metal organic vapor-phase epitaxy approaches in this work.…”
Section: Photovoltaic Applicationsmentioning
confidence: 99%
“…In this approach, a QD superlattice is embedded in a semiconductor matrix with a larger band gap. In this direction, Marrón et al studied the potential formation of an intermediate band, by the insertion of CIS, CISe, CuGaS 2 , or CuGaSe 2 NCs in a host material, and concluded that defects may impose limits to the practical realization of QD-based intermediate band devices with these materials. ,, Ojajärvi et al studied the formation of an intermediate band structure by inserting CISe QDs within a CuGaS 2 matrix and calculated that this structure could provide a maximum PCE of 61% . The experimental feasibility of the growth of this nanocomposite was further demonstrated by molecular beam epitaxy and metal organic vapor-phase epitaxy approaches in this work.…”
Section: Photovoltaic Applicationsmentioning
confidence: 99%
“…Tetragonal chalcopyrites with a general formula of II–IV–V 2 continue to be of interest for a variety of applications, including optoelectronics and photovoltaics, nonlinear optics, topological insulators, and spintronics. , Tetragonal ternary arsenides with lower-mass cations, i.e., II = Zn and IV = Si or Ge, have been the primary focus in the search for materials with specific properties of interest for these applications. Moreover, these materials have been reported to possess low phonon group velocities and large Gruneisen parameters, which would indicate relatively low lattice thermal conductivities for this material system . Most recently, the thermoelectric properties of antimony-based materials have also begun to be investigated. , Nevertheless, these materials have been investigated far less than chalcogenide compositions.…”
Section: Introductionmentioning
confidence: 99%
“…Chalcopyrite CuFeS2 belongs to the class of magnetic semiconductors that allow, by varying their chemical composition and structure, to obtain materials with a wide range of physical characteristics, such as band gap, type of conductivity, specific electrical conductivity, etc. These materials can be used as solar cells, coherent and incoherent sources of polarized radiation, in photovoltaic, thermoelectric and spintronic devices [1][2][3][4][5][6][7]. Thin films [8], nanowires and spherical particles [9,10], and nanocrystals [11][12][13] were synthesized.…”
Section: Introductionmentioning
confidence: 99%